Boosting Electrochemical Carbon Dioxide Reduction on Atomically Dispersed Nickel Catalyst - Hao, Qi; Liu, Dong-Xue; Deng, Ruiping; Zhong, Hai-Xia (Frontiers in Chemistry, 2022)
Single-atom catalysts (SACs) with metal-nitrogen (M-N) sites represent one of the most promised electrocatalysts for electrochemical carbon dioxide reduction (ECO2R). However, challenge in simultaneously enhancing the activity and selectivity greatly limit the efficiency of ECO2R due to the improper interaction of reactants/intermediates on these catalytic sites. Herein, we report a carbon-based nickel (Ni) clusters catalyst containing both single-atom and clusters sites (NiNx-T, T=500 to 800) through a ligand-mediated method, and realize a highly active and selective electrocatalytic CO2R process. The catalytic performance can be regulated by the dispersion of Ni-N species via controlling the pyrolysis condition. Benefitting by the synergistic effect of pyrrolic-nitrogen coordinated Ni single-atom and cluster sites, NiNx-600 exhibits a satisfying catalytic performance including a high partial current density of 61.85mA cm-2 and a high turnover frequency (TOF) of 7291 h-1 at -1.2 V vs. RHE, and almost 100 % selectivity toward carbon monoxide (CO) production, as well as good stability under 10 h of continuous electrolysis. This work discloses the significant role of regulating the coordination environment of the transition metal sites, and the synergistic effect between isolated single-site and cluster site in enhancing ECO2R performance.